Bacterial Contamination of Stethoscope in a Tertiary Care Hospital (TAJ: Journal of Teachers Association, 2018)
Bacterial contamination of stethoscope and its role in transmission of nosocomial infection is little known among the healthcare workers of Bangladesh. The objectives of our study is to evaluate stethoscope handling and cleaning practices, to find out the bacterial agents contaminating the stethoscopes, to determine the antibiotic sensitivity patterns of bacterial isolates from stethoscopes, and to evaluate the relationship between stethoscope cleaning practices with contamination of stethoscope in Rajshahi Medical College Hospital. This observational cross sectional study was carried out in Rajshahi Medical College Hospital during March, 2017. One hundred doctors working in different departments of RMCH were chosen randomly and were asked to fill up a self-explanatory simple questionnaire. Samples from100 stethoscopes were obtained after swabbing the diaphragm and the bell of the stethoscope with a sterile swab moistened with saline. These swabs were immediately streaked onto blood agar, Mcconkey agar and chocholate agar following the standard protocol. Out of 100 stethoscopes examined for bacterial contamination, 19 stethoscopes (19%) were found to be contaminated. The organisms isolated were MRSA, pseudomonas aeruginosa, and E. coli. Among the 19 participants with bacterial contamination of stethoscope, 6 doctors (31.6%) said they used to clean their stethoscope at least occasionally and 13 doctors (68.4%) had never cleaned their stethoscope. This difference was found to be statistically significant (p value